2008
DOI: 10.1039/b715947a
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of a heterocyclic As–Se compound with metal salts: syntheses and structures of the first copper complexes and of new alkali metal salts containing As–Se anions

Abstract: The structures of the new compounds [Cu8(Ph2As2Se2)2(PhAsSe2)2(dppm)4] (1) (dppm = bis-diphenylphosphinomethane), [Cu4(Ph2As2Se2)2(PPh3)4] (2), [{K(18-crown-6)}2(PhAsSe3)] (3), [Na12(PhAsSe3)6(15-crown-5)6] (4) and 1/x[Na2(PhAsSe3)(thf)(H2O)3]x (5) are reported. 2-5 were prepared by reactions of metal thiolates with [(PhAs)2(mu-Se)(mu-Se2)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Synthesis of transition metal arsenides in solution is challenging due to difficulties in solubilizing elemental arsenic . However, synthesis of transition metal chalcogenidoarsenates has been achieved by solution-based approaches. A majority of such organic–inorganic hybrid compounds contain arsenic not as a part of the transition metal-chalcogenide framework but as charge-balancing selenoarsenate anions. Sheldrick and co-workers synthesized a series of manganese selenoarsenate compounds with terpyridine ligands. Non-centrosymmetric molecular arsenic selenides, such as As 4 Se 4 ( D 2 d ) and As 4 Se 3 ( C 3 v ) are more soluble than elemental arsenic. Consequently, they have been used as precursors to synthesize hybrid selenoarsenates. Ansari et al reported that dissolution of As 4 Se 4 in amine solvents cleaves As–As bonds to form As 4 Se 6 2– ( D 2 d ), and in the presence of excess polyselenide anions, this ion further fragments, resulting in the formation of As 2 Se 6 2– ( C i ) with exocyclic As–Se bonds. , Furthermore, reports by Ibers et al showed how [As x Se y ] z − anions can be extracted from metal arsenic selenides using ammonia and ethylenediamine. , These anionic motifs can combine with transition metals in solution to form extended structures.…”
Section: Introductionmentioning
confidence: 99%
“…Synthesis of transition metal arsenides in solution is challenging due to difficulties in solubilizing elemental arsenic . However, synthesis of transition metal chalcogenidoarsenates has been achieved by solution-based approaches. A majority of such organic–inorganic hybrid compounds contain arsenic not as a part of the transition metal-chalcogenide framework but as charge-balancing selenoarsenate anions. Sheldrick and co-workers synthesized a series of manganese selenoarsenate compounds with terpyridine ligands. Non-centrosymmetric molecular arsenic selenides, such as As 4 Se 4 ( D 2 d ) and As 4 Se 3 ( C 3 v ) are more soluble than elemental arsenic. Consequently, they have been used as precursors to synthesize hybrid selenoarsenates. Ansari et al reported that dissolution of As 4 Se 4 in amine solvents cleaves As–As bonds to form As 4 Se 6 2– ( D 2 d ), and in the presence of excess polyselenide anions, this ion further fragments, resulting in the formation of As 2 Se 6 2– ( C i ) with exocyclic As–Se bonds. , Furthermore, reports by Ibers et al showed how [As x Se y ] z − anions can be extracted from metal arsenic selenides using ammonia and ethylenediamine. , These anionic motifs can combine with transition metals in solution to form extended structures.…”
Section: Introductionmentioning
confidence: 99%